Epistemology of Biology Education in The Technology Era: from Real Experiments to Virtual Laboratories - Duprah, Nur Awaliah; Ismail, Ismail (Universitas Negeri Makassar, 2025)
Abstract. Digital transformation in biology education has resulted in fundamental changes in how scientific knowledge is understood, constructed, and validated by students. This article examines new directions in the epistemology of biology education through a review of 24 articles discussing epistemic cognition, epistemic practices, the use of virtual laboratories, and the shift from real experiments to digital environments. The research method used a literature review with thematic analysis on three focuses: the epistemology of biology education in the technological era, the reconstruction of experimental experiences in virtual laboratories, and the epistemological implications of using technology in biology learning. The results of the study show that technology changes the representation of knowledge and influences the way students interpret evidence, construct arguments, and understand scientific processes, as indicated by the analysis of 24 articles, around 60% of which highlight the shift in experimental practices from real laboratories to virtual laboratories. Virtual laboratories offer advantages in terms of accessibility, visualization, and variable control, but pose epistemic challenges related to the validity of evidence and the potential for misrepresentation. This study emphasizes the need for a hybrid epistemological approach that integrates direct empirical experience with technology-based learning to shape epistemic literacy relevant to the demands of the digital age. Keywords: biology education, digital epistemology, epistemic cognition,, virtual laboratory